Соціально-економічний механізм ефективного використання ресурсів рекреаційної сфери в контексті сталого розвитку - Куценко, В.І.; Трілленберг, Г.І. (Економіка природокористування і охорони довкілля, 2013)
Розкривається сутність сталого розвитку, його основні складові, місце і роль природних ресурсів у його забезпеченні. Обґрунтовуються складові соціально-економічного механізму ефективного використання рекреаційних ресурсів для забезпечення сталого розвитку. Served the changes that occurred in the socio-economic development of Ukraine. Been singled out tourism and recreation area that, on the one hand, has enormous resources for its development, and secondly, it is in the economy of our country is inadequate space.
Provision factors (objective and subjective) that causes this. In this paper, special attention is paid to the resources that are the basis of development of tourism and recreation industry. It is emphasized that almost all regions have both natural and cultural and historical resources. However, they are not used efficiently. Because the work is socio-economic mechanism that ensures efficient use of these resources. Among the elements of this mechanism serves such as the industry's transition to an innovative way of development, cluster approach and so on. Reported that the clustering of tourism and recreation improves quality tourist and recreational services, promotes the development of small business in this area, expanding opportunities to enter the international market, increase the competitiveness of products, to accelerate sustainable socio-economic development.